The prophetic quest : the stained glass windows of Jacob Landau, Reform Congregation Keneseth Israel, Elkins Park, Pennsylvania - Herrstrom, David S. (Dimyonot: Jews and the cultural imagination, 2021)
"Explores ten monumental stained-glass windows, designed by the artist Jacob Landau, for the Keneseth Israel synagogue in Elkins Park, Pennsylvania"--